A fully human anti-c-Kit monoclonal antibody 2G4 inhibits proliferation and degranulation of human mast cells - Kim, Kwang Hyeok; Kim, Jin Ock; Park, Sang Gyu (Molecular and Cellular Biochemistry, 2023)
Given that mast cells are pivotal contributors to allergic diseases, various allergy treatments have been developed to inhibit them. Omalizumab, an anti-immunoglobulin E antibody, is a representative therapy that can alleviate allergy symptoms by inhibiting mast cell degranulation. However, omalizumab cannot reduce the proliferation and accumulation of mast cells, which is a fundamental cause of allergic diseases. c-Kit is essential for the proliferation, survival, and differentiation of mast cells. Excessive c-Kit activation triggers various mast cell diseases, such as asthma, chronic spontaneous urticaria, and mastocytosis. Herein, we generated 2G4, an anti-c-Kit antibody, to develop a therapeutic agent for mast cell diseases. The therapeutic efficacy of 2G4 antibody was evaluated in LAD2, a human mast cell line. 2G4 antibody completely inhibited c-Kit signaling by blocking the binding of stem cell factor, known as the c-Kit ligand. Inhibition of c-Kit signaling led to the suppression of proliferation, migration, and degranulation in LAD2 cells. Moreover, 2G4 antibody suppressed the secretion of pro-inflammatory cytokines, including granulocyte–macrophage colony-stimulating factor, vascular endothelial growth factor, C–C motif chemokine ligand 2, brain-derived neurotrophic factor, and complement component C5/C5a, which can exacerbate allergy symptoms. Taken together, these results suggest that 2G4 antibody has potential as a novel therapeutic agent for mast cell diseases.
Keywords: Cell Degranulation; Cell Proliferation; Humans; Hypersensitivity; Mast Cell Activation Disorders; Mast Cells; Omalizumab; Proto-Oncogene Proteins c-kit; Receptor Protein-Tyrosine Kinases; Stem Cell Factor; Vascular Endothelial Growth Factor A; Allergy; c-Kit; Mast cell; Mast cell disease; Monoclonal antibody